Harmoni dibawah Naungan Mbah Agung - Nikmah, Shofiatun; Ikhsan, M. Samsul (Proceedings of Annual Conference for Muslim Scholars, 2024)
In the multicultural community of Dorok Hamlet, the Grebek Suro tradition, conducted under the Beringin Mbah Agung tree (a sacred site), serves as a significant symbol in strengthening interfaith harmony and ecological awareness. This study aims to deeply examine how the Grebek Suro tradition functions as a form of education and reinforcement for social harmony among religious communities while fostering ecological consciousness. This research is qualitative in nature, employing a phenomenological approach. Data were collected through interviews, observations, and document analysis. The findings reveal that the Grebek Suro tradition not only possesses spiritual dimensions but also conveys messages about ecological responsibility. Practices of tolerance and mutual cooperation within this tradition affirm principles of mutual respect and collaboration, which are central to Islamic teachings. The practice of venerating the tree also fosters ecological awareness, promoting coexistence with, and care for, nature. Meanwhile, the practice of collective prayer led by three religious leaders (Christian, Catholic, and Muslim) teaches principles of equality and mutual respect, which are also core values in Islamic teachings. Thus, this study explores the role of local traditions in cultivating values of tolerance and ecological awareness, as well as their contribution to social harmony in Dorok Hamlet.